Internalisasi Nilai-Nilai Etika Hindu di Komunitas Ekspresi Desa Sibang Kaja Kabupaten Badung - Ramadi Putra, I Komang; Uma Lestari, Ni Putu Prawani; Ariasa Giri, I Made; Sariani Binawati, Ni Wayan; Suyanta, I Wayan (Metta : Jurnal Ilmu Multidisiplin, 2023)
Dharma is a principle of life that every human being must own. Dharma in the form of behavior is called Susila (ethics). Komunitas Ekspresi in every activity always emphasizes and instills ethical values in children. From a conceptual point of view, the internalization of ethical values in the Komunitas Ekspresi is similar to Hindu ethical values. This study aimed to describe the internalization of Hindu ethical values in the Komunitas Ekspresi of Sibang Kaja Village, Badung Regency. The research method used is qualitative with an ethnographic approach a la James Spradley. The technique for determining informants is purposive sampling following the ethnographic method. Types and sources of data are qualitative data types, while data sources are primary and secondary data. Data collection techniques are observation, interviews, and documentation studies. Ethnographic data analysis techniques, namely domain analysis, taxonomic analysis, componential analysis, and analysis of cultural themes. The results of this study found that: 1) Internalization of Hindu ethical values found were: a) Law of Karma, namely children are taught to be responsible for what they do, b) Catur Guru, namely children are taught to respect four teachers, c) Tri hita karana, namely children are taught to establish harmonious relationships with God, fellow human beings and the environment, d) Catur Paramita, namely children are taught to apply the four ethical attitudes of noble character. 2) The inhibiting factors for internalizing Hindu ethical values include a) parental support, which is relatively low, especially in assisting in continuing the direction of teaching staff in educating children when they are at home, b) teaching staff whose number is still limited and c) facilities which are still classified as limited. 3) The impact of internalizing Hindu ethical values is the religious impact, the emotional impact, the impact of independent behavior, the impact of responsibility, the impact of self-confidence, and the impact of creativity. The conclusion is that the Komunitas Ekspresi teaches Hindu ethical values.